The E-Twenty-Six Family in Hepatocellular Carcinoma: Moving into the Spotlight - Zhang, Tongyue; Liu, Danfei; Wang, Yijun; Sun, Mengyu; Xia, Limin (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is a major cause of morbidity and mortality worldwide. Although therapeutic strategies have recently advanced, tumor metastasis and drug resistance continue to pose challenges in the treatment of HCC. Therefore, new molecular targets are needed to develop novel therapeutic strategies for this cancer. E-twenty-six (ETS) transcription family has been implicated in human malignancies pathogenesis and progression, including leukemia, Ewing sarcoma, gastrointestinal stromal tumors. Recently, increasing studies have expanded its great potential as functional players in other cancers, including HCC. This review focuses primarily on the key functions and molecular mechanisms of ETS factors in HCC. Elucidating these molecular details may provide novel potential therapeutic strategies for cancers.